Нові та маловідомі для України види кортиціоїдних грибів - Ординець, О.В.; Юрченко, Є.О. (Український ботанічний журнал, 2010)
Сообщается о восьми видах кортициоидных грибов, выявленных в 2007 и 2009 годах на территории Национального природного парка «Святые горы» (Донецкая обл.). Из них три вида — Hypochniciellum ovoideum (Jülich) Hjortstam et Ryvarden, Trechispora alnicola (Bourdot et Galzin) Liberta и T. stevensonii (Berk. et Broome) K.H. Larss. — являются новыми для Украины. Другие пять видов впервые обнаружены на Левобережье и равнинной части страны. Для всех видов приведены описания исследованных образцов и иллюстрации. Обсуждаются их экологические особенности, распространение и степень редкости. Eight species of corticioid fungi found in 2007 and 2009 on the territory of «Sviati Hory» National Nature Park (Donetsk Region) are considered. Three of them, Hypochniciellum ovoideum (Jьlich) Hjortstam et Ryvarden, Trechispora alnicola (Bourdot et Galzin) Liberta and T. stevensonii (Berk. et Broome) K.H. Larss., are new records for Ukraine. Other five species are first reported for the Leftbank area as well as for the plain area of Ukraine. For all the species, descriptions of the specimens studied and their illustrations are provided. Information on ecology, distribution and rarity of these species worldwide is also discussed.